2005
DOI: 10.2188/jea.15.219
|View full text |Cite
|
Sign up to set email alerts
|

Factors Explaining Disability-free Life Expectancy in Japan: the Proportion of Older Workers, Self-reported Health Status, and the Number of Public Health Nurses

Abstract: Statistical analysisFirst, for descriptive observations and screening purposes, distributions of the selected variables were studied using histograms. Log-transformation was performed for the skewed variables of population density and unemployment rate. Then, correlation coefficients between DFLE65s of men and women and independent variables were calculated. For the correlation analyses, Pearson's product moment correlation coefficient or Spearman's rank correlation coefficient were used for the independent va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
1
19
0
1
Order By: Relevance
“…From this question, we created a dichotomous outcome measure with poor perceived health if the respondent answered fair or poor. It has been reported that self-rated health is associated with various objective health measures and strongly predicts future onset of mortality (Idler & Benyamini, 1997; Kondo et al, 2005; Kopp, Skrabski, Rethelyi, Kawachi, & Adler, 2004). …”
Section: Methodsmentioning
confidence: 99%
“…From this question, we created a dichotomous outcome measure with poor perceived health if the respondent answered fair or poor. It has been reported that self-rated health is associated with various objective health measures and strongly predicts future onset of mortality (Idler & Benyamini, 1997; Kondo et al, 2005; Kopp, Skrabski, Rethelyi, Kawachi, & Adler, 2004). …”
Section: Methodsmentioning
confidence: 99%
“…association between self-rated health and preference of the place of death; however, some reports have focused on the association of self-rated health with mobility disabilities 25 , disabilities in basic activities of daily living 26 , quality of life 27 , and disability-free life expectancy 28 . Thus, a person with good self-rated health probably also has good mobility function and quality of life, which may alleviate worry about admission to a medical institution or longterm care facility in the near future.…”
Section: Tablementioning
confidence: 99%
“…Recently, growing attention has been paid to the potential determinants of health and remaining life expectancy, in particular among elderly Japanese individuals. However, most of these studies were performed using cross-sectional and ecological data [4,5]. As such, it was quite difficult to analyze causal effects on individual elderly health conditions over the life span due to the limitations posed by cross cutting and the ecological fallacy.…”
Section: Introductionmentioning
confidence: 99%